2020
DOI: 10.18203/2349-2902.isj20200828
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate the safety and cost effectiveness of preformed catgut endoloops and polyglactin 910 extracorporeal ligation in the management of appendicular stump closure in laparoscopic appendicectomy

Abstract: Background: The most essential component of laparoscopic appendectomy is the closure of appendicular stump. Failure of which can result in catastrophic complications including intra-abdominal and surgical site infections and rarely faecal fistula. The aim of this study was to verify the effectiveness of preformed catgut endoloop and extracorporeal polyglactin 910 for appendicular stump closure.Methods: This prospective study was carried out in 64 patients. We compared patient demographics, duration of surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A sliding knot can be formed using a simple tie, and inserted through a 5 mm trocar, 31 and can then be manipulated by two instruments, rather than one. 32,33 There are no RCTs assessing the difference between an ECK and other closure methods. However, a combination of retrospective and prospective studies have shown that the tying of an extracorporeal knot is not associated with increased operative time compared to polymeric clip 34 or stapler.…”
Section: Appendiceal Stump Closurementioning
confidence: 99%
See 1 more Smart Citation
“…A sliding knot can be formed using a simple tie, and inserted through a 5 mm trocar, 31 and can then be manipulated by two instruments, rather than one. 32,33 There are no RCTs assessing the difference between an ECK and other closure methods. However, a combination of retrospective and prospective studies have shown that the tying of an extracorporeal knot is not associated with increased operative time compared to polymeric clip 34 or stapler.…”
Section: Appendiceal Stump Closurementioning
confidence: 99%
“…A sliding knot can be formed using a simple tie, and inserted through a 5 mm trocar, 31 and can then be manipulated by two instruments, rather than one. 32,33…”
Section: Appendiceal Stump Closurementioning
confidence: 99%